Identifikasi Infeksi Virus Pada Tubuh Buah Jamur Shiitake (Lentinula edodes) Menggunakan Metode Teknologi Molekuler - Mustikasari, Fauzia (Faculty of Agriculture Universitas Singaperbangsa Karawang, 2023)
ABSTRACT Lentinula edodes (shiitake) is one of the most produced mushrooms in China. Not only famous with its medicinal value but also with its unique taste. Shiitake’s growth and fruit body formation influenced by many factors including biological, chemical, and physical factors. Virus infection in mushroom especially in shiitake is a relatively new. Whether virus infection caused severe disease or just reside inside basidiocarp and mycelium without causing any abnormality or physiological change are still unclear. This research was conducted to discover is there any relationship between abnormal fruit body with virus infection. Study used molecular genetics method to prove relationship between them. RT-PCR conducted to prove which sample contain the virus, BLAST sequence result showed that there is no significant similarity found with other sequences in NCBI data. Because of very low quantity of virus, unsuitable primer used to detect viral sequence, or new sequences of viral material genetic that has not registered in NCBI. Many factors influence the formation of fruit body including genetic and environmental factors. Abnormalities maybe caused by environmental factor while virus infected shiitake were not discovered. Keywords: abnormal shiitake basidiocarp; shiitake mycovirus; cultivate mushroom